Christopher St German on Scripture, councils, and monarchs. Issue 3 (1st November 2014) - Rex, Richard
Abstract This article explores the idiosyncratic reflections on ecclesiastical and royal power in England sketched out in a little known manuscript by the Tudor lawyer and publicist, Christopher St German (d.1540/41). His unpublished 'Dyalogue shewinge What we be bounde to byleve as thinges necessary to salvacion' investigated the question of ecclesiastical authority with respect to Christian doctrine. Its argument hinged on a unique interpretation of the Matthaean 'binding and loosing' texts (Mt.16:19; 18:18) that was designed to identify the point in history at which ecclesiastical authority was transferred from bishops to kings. It is proposed here that the ulterior motive was to insulate Christian monarchs in general (and the king of England in particular) from the impact of any ecclesiastical power, be it papal or conciliar.